2013
DOI: 10.1037/a0032400
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of negative and positive affect in daily life.

Abstract: Emotion regulation has primarily been studied either experimentally or by using retrospective trait questionnaires. Very few studies have investigated emotion regulation in the context in which it is usually deployed, namely, the complexity of everyday life. We address this in the current paper by reporting findings of two experience-sampling studies (Ns = 46 and 95) investigating the use of six emotion-regulation strategies (reflection, reappraisal, rumination, distraction, expressive suppression, and social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

61
523
12
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(601 citation statements)
references
References 74 publications
61
523
12
5
Order By: Relevance
“…These results were consistent with past research that reported the frequent use of music to enhance mood (Juslin and Laukka, 2004;North et al, 2000) and cope with symptoms of stress (Bradt and Dileo, 2009). Despite finding that greater negative affect predicted increased use of emotion regulation strategies, Brans et al (2013) also reported that use of adaptive strategies such as reappraisal did not predict subsequent change in negative affect. The latter finding is in contrast to several other reports, which have linked the use of cognitive reappraisal with diminished negative affect and lower levels of psychopathology symptoms (Aldao et al, 2010;Gross and John, 2003;Haga et al, 2009;John and Gross, 2004).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results were consistent with past research that reported the frequent use of music to enhance mood (Juslin and Laukka, 2004;North et al, 2000) and cope with symptoms of stress (Bradt and Dileo, 2009). Despite finding that greater negative affect predicted increased use of emotion regulation strategies, Brans et al (2013) also reported that use of adaptive strategies such as reappraisal did not predict subsequent change in negative affect. The latter finding is in contrast to several other reports, which have linked the use of cognitive reappraisal with diminished negative affect and lower levels of psychopathology symptoms (Aldao et al, 2010;Gross and John, 2003;Haga et al, 2009;John and Gross, 2004).…”
Section: Discussionsupporting
confidence: 81%
“…This suggests that observed beneficial mental health outcomes were uniquely accounted for by music use for cognitive and emotional purposes, through the use of cognitive reappraisal emotion regulation strategy, and not the disposition to experience positive feelings and moods. In addition, Brans et al (2013) found that high levels of positive affect predicted lesser use of cognitive reappraisal as an emotion regulation strategy. By including trait positive affect as a covariate in the current mediation analysis, this allowed us to clearly distinguish unique contributions of music use for cognitive and emotional regulation on both cognitive reappraisal as an emotion regulation style and mental health outcomes, from the potential influence of trait positive affect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for why distressing shifts elicited higher levels of perseverative cognition is that distressing shifts are more emotionally charged than workload and induce a higher degree of negative affect. Research has shown that daily events that evoke a higher degree of negative affect induce a higher level of perseverative cognition too 34) . In line with our third hypothesis, perseverative cognition was associated with delayed sleep onset.…”
Section: Discussionmentioning
confidence: 99%
“…Jej natężenie reguluje poziom dobrostanu u funkcjonariuszy służby więziennej. Zdolność do kontrolowania emocji wpływa na funkcjonowanie psychospołeczne i rozwój zawodowy [18].…”
Section: Wynikiunclassified